Collective control strategy for a cluster of stall-regulated offshore wind turbines. (January 2016) - Hur, S.; Leithead, W.E.
Abstract: The power converter is one of the most vulnerable components of a wind turbine. When the converter of an offshore wind turbine malfunctions, it could be difficult to resolve due to poor accessibility. A turbine generally has a dedicated controller that regulates its operation. In this paper, a collective control approach that allows a cluster of turbines to share a single converter, hence a single controller, that could be placed in a more accessible location. The resulting simplified turbines are constant-speed stall-regulated with standard asynchronous generators. Each cluster is connected by a mini-AC network, whose frequency can be varied through a centralised AC–DC–AC power converter. Potential benefits include improved reliability of each turbine due to simplification of the turbines and enhanced profit owing to improved accessibility. A cluster of 5 turbines is assessed compared to the situation with each turbine having its own converter. A collective control strategy that acts in response to the poorest control is proposed, as opposed to acting in response to the average control. The strategy is applied to a cluster model, and simulation results demonstrate that the control strategy could be more cost-effective than each turbine having its own converter, especially with optimal rotor design. Highlights: We propose a collective control strategy for offshore wind farms. A set of single converter and controller is shared between 5 turbines. The strategy acts in response to the poorest performing turbines when necessary. The strategy could improve reliability of each turbine and be cost-effective. Accessibility to the turbines could be improved.